PROTECTIVE EFFECTS OF ETHYL ACETATE EXTRACTION FROM GASTRODIA ELATA BLUME ON BLOOD-BRAIN BARRIER IN FOCAL CEREBRAL ISCHEMIA REPERFUSION - He, Fangyan; Duan, Xiaohua; Dai, Rong; Wang, Wei; Yang, Cui; Lin, Qing (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Damage of the blood brain barrier (BBB) during the process of cerebral ischemic injury is a key factor whichinfluences the therapeutic efficacy to the cerebral ischemic injury. The present study was designed to verify the mechanismsunderlying the protective effects of the ethyl acetate (EtOAc) extraction from Gastrodia elata Blume (GEB) on the BBB bydeveloping a model of cerebral ischemia-reperfusion in rats. Material and methods: MCAO/R model in rats was developed througha thread embolism method. The neurological scales, the moisture and the evans blue (EB) contents of brains were detected.Meanwhile, the release of nitric oxide (NO) and activities of NO synthase (NOS) in brain tissues were measured. Western blottinganalyses were also performed to assess the protein expressions of AQP-4, Occludin and Claudin-5 in brain tissue. Result: After ratswere pretreated with different concentrations of EtOAc extractions from GEB, the neurologic scores, the EB contents in the braintissues and the moisture of the brains were significantly decreased. Meanwhile, the release of NO, the activities of nNOS and iNOSwere notably inhibited. Furthemore, the protein expression of AQP-4 was markedly decreased, but the protein expressions ofClaudin-5 and Occludin were significantly increased. Conclusion: the EtOAc extracts of GEB may decrease the permeability ofBBB when focal cerebral ischemia occurs. The inhibition of the NOS pathways, the attenuation of the protein expression of AQP-4and the enhancement of the expressions of the tight junction proteins may contribute to the protective effects of the EtOAc extractsfrom GEB on BBB.